2002
DOI: 10.1073/pnas.112677599
|View full text |Cite
|
Sign up to set email alerts
|

1 H and 13 C MAS NMR evidence for pronounced ligand–protein interactions involving the ionone ring of the retinylidene chromophore in rhodopsin

Abstract: Rhodopsin is a member of the superfamily of G-protein-coupled receptors. This seven ␣-helix transmembrane protein is the visual pigment of the vertebrate rod photoreceptor cells that mediate dim light vision. In the active binding site of this protein the ligand or chromophore, 11-cis-retinal, is covalently bound via a protonated Schiff base to lysine residue 296. Here we present the complete 1 H and 13 C assignments of the 11-cis-retinylidene chromophore in its ligand-binding site determined with ultra high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
184
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(203 citation statements)
references
References 51 publications
17
184
1
1
Order By: Relevance
“…Such a 6s-cis structure is characterized by a substantial negative twist of the dihedral angle (-44°) at the C6-C7 bond. 1 These theoretical results are partially consistent with recent NMR studies 43,44 and with the analysis of the recently resolved X-ray structure at 2.2 Å resolution. 5 7.3.…”
Section: Orientation Of the -Ionone Ringsupporting
confidence: 87%
See 3 more Smart Citations
“…Such a 6s-cis structure is characterized by a substantial negative twist of the dihedral angle (-44°) at the C6-C7 bond. 1 These theoretical results are partially consistent with recent NMR studies 43,44 and with the analysis of the recently resolved X-ray structure at 2.2 Å resolution. 5 7.3.…”
Section: Orientation Of the -Ionone Ringsupporting
confidence: 87%
“…An important aspect addressed by recent DFT QM/MM simulations 2 is the observed upfield shift of σ C at C5, which has been previously assigned to the interaction between C5 and the carboxylic group of Glu-122. 43 However, QM/ MM calculations indicate that the electrostatic influence of Glu-122 is negligible when such a residue is protonated as suggested by FTIR experiments. 49 In contrast, QM/MM studies found that the most significant upfield shift on C5 is due to Trp-265, with an upfield effect of -2.0 ppm.…”
Section: Orientation Of the -Ionone Ringmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the lightactivated Meta II state is transient and crystal deformation occurs giving low-resolution data (14). Crystal structures of ligand-free opsin (19) with a bound synthetic G t peptide (20) show an elongation of the protein (21, 22) due to helical displacements (19)-but opsin does not contain the activating all-trans-retinal ligand, and its activity does not match rhodopsin (20).Spectroscopic approaches including spin-label EPR (23), 13 C NMR (18,(24)(25)(26), and Fourier transform infrared (FTIR) (17, 27) studies are thus needed to establish the activation mechanism of the photoreceptor as it underlies the visual process. Solid-state NMR spectroscopy (28) is particularly important, as it gives knowledge of both protein structure and dynamics in a membrane lipid environment (29).…”
mentioning
confidence: 99%